ANALISIS PENYELESAIAN SENGKETA DALAM TRANSAKSI BISNIS INTERNASIONAL MELALUI ARBITRASE - Sandy Wiratno H Simanjuntak (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze dispute resolution in international business transactions through arbitration as one of the alternative dispute resolution mechanisms widely used in global trade practices. The increasing number of crossborder transactions has given rise to various dispute potentials due to differences in legal systems, jurisdictions, languages, and the economic interests of the parties involved. In such circumstances, arbitration serves as a dispute resolution forum considered more effective than litigation because it is flexible, confidential, efficient, and produces final and binding decisions. This research employs a normative legal research method with statutory, conceptual, and case approaches. The data sources consist of primary, secondary, and tertiary legal materials obtained through library research. The findings indicate that arbitration holds a highly significant position in resolving international business disputes as it provides legal certainty and neutrality for parties from different countries. The arbitration mechanism begins with the inclusion of an arbitration clause in the contract, followed by the filing of a claim, the formation of an arbitral tribunal, case examination, and the enforcement of the award. Nevertheless, arbitration also has several weaknesses, such as relatively high costs, limited legal remedies, and obstacles in enforcing arbitral awards in certain countries. Therefore, arbitration remains the preferred mechanism for resolving international business disputes as long as it is supported by clear contractual clauses and a supportive legal system.